Late Holocene palaeo-environmental change in the Banni Plains, Kachchh, Western India. (25th February 2019) - Makwana, Nisarg; Prizomwala, S.P.; Chauhan, G.; Phartiyal, Binita; Thakkar, M.G.
Abstract: The effect of the environmental change during the Middle to Late Holocene period, on the demise of the mighty Harappan civilization has remained a topic of debate. The western India, especially the coastal regions, hosted a cluster of Harappan settlements near the shoreline. The present study attempts to reconstruct the evolution of Banni Plains of the Kachchh region, which has remained a hotspot for Harappan civilization. We employed a host of multi-proxy techniques viz., sedimentology, sediment geochemistry, magnetic susceptibility along with OSL chronology, to deduce the palaeo-environmental changes experienced by the Banni Plains from a shallow 4.05 m deep trench. The four OSL chronology of the sediments suggests the time span of 2.9 ka to 0.2 ka, revealing a first hand estimate of average sedimentation rate of 1.5 mm per annum. The enhanced chemical weathering intensities suggest that the last two millennia witnessed two phases of relatively warm and humid climatic conditions, which probably coincide with the Roman Warm Period (?) and the Medieval Warm Period (?). The Banni Plains was evolved owing to the Middle Holocene high sea stand and subsequent relative fall during the last 2 ka period. The extent of the relative high sea stand upto 2 m above msl also corroborated well by ancient port settlements of the Late Harappan period. This implies that the Harappan civilization was indeed influenced and affected by the past sea level change; nevertheless, this cannot be the sole reason for demise of the mighty civilization, but remained an auxiliary mechanism along with aridity which severed the human adaptation.